Frequency of Anxiety, Depression and Stress among Pharmacy Undergraduates of Annual and Semester System: A Cohort-Based Comparison - Azam, Mehmood; Ishaq, Rabia; Iqbal, Qaiser; Jan, Syed Umer; Mengal, Mohammad Alam; Saleem, Fahad (Journal of Pharmacy Practice and Community Medicine)
Objectives: The current study was aimed to evaluate the anxiety, depression and stress (AD&S) among two different academic performance systems (i.e. semester and annual system). Methods: A questionnaire— based, cross-sectional survey technique was adopted. The Depression, Anxiety and Stress Scale (DASS) was used to assess the AD&S among pharmacy undergraduates enrolled at Faculty of Pharmacy and Health Sciences, University of Balochistan Quetta. SPSS v 20.0 was used for data coding and analysis whereas both descriptive and inferential statistics were used for data elaboration. Results: Two hundred and eighty-nine pharmacy undergraduates participated in the study with a distribution of 43.3% belonging to the annual academic system and 56.7% from the semester system. Students Majority were of 20 years old (59, 20.4%), including both male (194, 67.1%) and female (95, 32.9%). The mean AD&S scores of the entire cohort were 14.15±9.3, 13.61±7.9 and 18.18±8.2 respectively representing moderate AD&S among pharmacy undergraduates. Statistically significant difference (p<0.05) was reported among students of annual and semester system for all three variables of study whereby the students of semester system were more in AD&S as compared to the annual system. Conclusion: Based on the findings of current study it is suggested that measure should be taken to reduce the AD&S among students for better academic performance. This is achievable by engaging students by inquiring their queries and problems faced during the semester-related activities. By doing so, a stress-free environment is predicted hence bringing academic prosperity among students leading to the development of a more qualified and satisfied future pharmacist.
Keywords: Anxiety; Depression; Stress; Pharmacy; Undergraduates